2019
DOI: 10.1152/ajpendo.00194.2018
|View full text |Cite
|
Sign up to set email alerts
|

ER stress contributes to high-fat diet-induced decrease of thyroglobulin and hypothyroidism

Abstract: Recent studies revealed the emerging role of excess uptake of lipids in the development of hypothyroidism. However, the underlying mechanism is largely unknown. We investigated the effect of high-fat diet (HFD) on thyroid function and the role of endoplasmic reticulum (ER) in HFD-induced hypothyroidism. Male Sprague-Dawley rats were fed with HFD or control diet for 18 wk. HFD rats showed an impaired thyroid function, with decreased thyroglobulin (Tg) level. We found the ER stress was triggered in HFD rat thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…On the other hand, our previous reports had established the potential effects of excess lipid deposition to thyroid function, by which the probable mechanism was lipotoxicity-related endoplasmic reticulum (ER) stress or mitochondrial stress of thyrocytes, subsequently leading to thyroid dysfunction. This is an innovative point of view that had been confirmed in clinical study and laboratory research (Zhao et al, 2016 , 2018 ; Zhang et al, 2019 ). In this study, gut microbes, which had already been recognized as another important “endocrine factors,” was the focus to discover the possible association with SCH on clinical levels.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, our previous reports had established the potential effects of excess lipid deposition to thyroid function, by which the probable mechanism was lipotoxicity-related endoplasmic reticulum (ER) stress or mitochondrial stress of thyrocytes, subsequently leading to thyroid dysfunction. This is an innovative point of view that had been confirmed in clinical study and laboratory research (Zhao et al, 2016 , 2018 ; Zhang et al, 2019 ). In this study, gut microbes, which had already been recognized as another important “endocrine factors,” was the focus to discover the possible association with SCH on clinical levels.…”
Section: Discussionmentioning
confidence: 81%
“…The synthesis of misfolded Tg is accompanied by ER stress (38,(48)(49)(50)(51). Ongoing ER stress in the thyroids of TG cog/cog mice was demonstrable (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…By virtue of their highly secretory function, Paneth cells are characterized by extensive networks of ER and thus are particularly susceptible to increased ER stress response and autophagy ( 45 ). Prior reports have demonstrated that a HFD and obesity induce ER stress in different organ systems, including adipose tissue, the amygdala, and the thyroid gland ( 46 48 ). Guo et al reported increased mRNA expression of ER stress markers, including BiP , activating transcription factor 4 ( ATF4 ), and c/EBP-homologous protein ( CHOP ) in mice fed a HFD ( 49 ).…”
Section: Discussionmentioning
confidence: 99%